2021
DOI: 10.3389/fevo.2021.735350
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fatty Acids From Aquatic Prey Varies With Foraging Strategy

Abstract: Across ecosystems, resources vary in their nutritional composition and thus their dietary value to consumers. Animals can either access organic compounds, such as fatty acids, directly from diet or through internal biosynthesis, and the extent to which they use these two alternatives likely varies based on the availability of such compounds across the nutritional landscape. Cross-ecosystem subsidies of important dietary nutrients, like omega-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFA), may provide c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…Here, we explored this dichotomy in more detail, considering multiple aquatic and terrestrial insect orders as well as seasonal changes in the strength of FA separation between aquatic and terrestrial insects in a lake ecosystem. Emergent aquatic insects had higher mean PUFA content, specifically ALA, EPA, ARA, and DHA, than terrestrial insects, which is in line with previous studies on both river (Twining et al, 2019;Kowarik et al, 2021) and lake ecosystems (Mathieu-Resuge et al, 2021b;Twining et al, 2021b). Twining et al (2019) found higher ALA proportions in terrestrial Hymenoptera and Lepidoptera, but higher EPA proportions in aquatic insect taxa near streams in the Eastern United States during the 10.3389/fevo.2022.952292…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Here, we explored this dichotomy in more detail, considering multiple aquatic and terrestrial insect orders as well as seasonal changes in the strength of FA separation between aquatic and terrestrial insects in a lake ecosystem. Emergent aquatic insects had higher mean PUFA content, specifically ALA, EPA, ARA, and DHA, than terrestrial insects, which is in line with previous studies on both river (Twining et al, 2019;Kowarik et al, 2021) and lake ecosystems (Mathieu-Resuge et al, 2021b;Twining et al, 2021b). Twining et al (2019) found higher ALA proportions in terrestrial Hymenoptera and Lepidoptera, but higher EPA proportions in aquatic insect taxa near streams in the Eastern United States during the 10.3389/fevo.2022.952292…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, vascular terrestrial plants typically contain only C18-PUFA, such as linoleic acid (LIN; 18:2n-6) and α-linolenic acid (ALA; 18:3n-3), and lack the ability to synthesize LC-PUFA (Uttaro, 2006;Hixson et al, 2015). This ecosystem-based (i.e., aquatic compared to terrestrial) difference in primary producers' FA profiles is transferred to higher trophic levels and is also observed between the FA profiles of aquatic and terrestrial insects (Guo et al, 2018;Kowarik et al, 2021;Mathieu-Resuge et al, 2021b;Twining et al, 2021b).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The phenology of aquatic and terrestrial insect communities drives the seasonal availability of n-3 LCPUFA, which are important nutrients for a diversity of consumers reliant on insects, 33,54,55 including avian aerial insectivores. 11,14,56 We find that the peak biomass of aquatic insect emergence tends to occur earlier in the season and then declines in total output, whereas terrestrial insect biomass progressively increases throughout our observed season.…”
Section: Discussionmentioning
confidence: 99%